Determining the factors contributing to firms’ default using KMV-Merton model and logistic Regression / Anis Suhaina Amraa Amadul Aziz, Nur’ Amirah Abd Halim and Ili Izreen Mustapah - Amadul Aziz, Anis Suhaina Amraa; Abd Halim, Nur’ Amirah; Mustapah, Ili Izreen (2022)
The COVID-19 pandemic has severely impacted the economy. Many firms in Malaysia were forced to shut down their business. Therefore, it is significant to have an effective risk management. In this study, we assess the default probability of 32 Malaysian companies by employing the KMV-Merton model. The default probability of firms obtained from employing the KMV-Merton model is used in predicting the credit rating of each firm. The predicted credit rating then was compared with the actual credit rating obtained from the MARC website. Based on the comparison, we achieved an accuracy rate of 81.72%. The default probability is then used in the Logistic regression to determine the factors that are highly causing a firm to default. Based on the Logistic regression analysis, the Leverage Ratio is the most significant factor contributing to default. To be specific, the Leverage Ratio used in this study is the DEBT-TO-CAPITAL RATIO. Therefore, the Leverage Ratios are predicted to have a higher impact on default risk. In this study, we also found that the macroeconomic variables such as Inflation Rate and Exchange Rate to have an insignificant effect on the firms’ default. It is recommended for future researchers to add more financial ratios to have a more accurate result regarding the significant factors that contribute to the default of a firm.